Interpreting pelagic seabird population numbers in the Maltese Islands (Avocetta, 2017)
The Maltese islands host three species of pelagic seabirds, namely: Scopoli`s Shearwater Calonectris diomedea, Yelkouan Shearwater Puffinus yelkouan and Mediterranean Storm-petrel Hydrobates pelagicus melitensis. Annual censuses of the breeding popu lation of the three species have been carried out since 1983. Seabird censuses present some of the most demanding challenges of ornitho logical studies, and this is exceedingly so when attempts are made in counting the breeding population of underground nesting seabirds such as the shearwaters and storm-petrels. The majority of these species visit land only during the breeding season and do so under cover of darkness. They often nest in inaccessible places or nearly so. At specific periods in the breeding year, the colonies are visited by nu merous prospecting and non-breeding birds, greatly inflating the number of birds in the colony. Faced with all these variables, any figures presented from these censuses can only be considered, at best, as guesstimates. Without the necessary background knowledge of the bio logy and ecology of the species under study, in many cases, these censuses will result in greatly inflated figures as were recently reported for Malta, Lampedusa and Zembra. These over-estimated figures will inevitably lead to both short and long term negative implications on any conservation efforts undertaken for these species.
Keywords: pelagic seabirds; census methodologies; population estimates